Pembangunan Sistem Informasi Perencanaan Program Kerja Berbasis Web (Studi Kasus GKPMI Getsemani Sorong) - Stephanie Gloria Padoma, Patricia; Setiyawati, Nina (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
Good work program planning can have a big impact in improving the quality of service for the members of the Calvary Pentecostal Missionary Church in Indonesia, Sorong - West Papua. The results of the work program plan and the report of the realization program are still being carried out in a paper based causing its difficult to manage and control each work program that has either been implemented or not yet implemented. On this research for creation of web-based information systems that refer to the PDCA (Plan, Do, Check, and Act) are expected to provide solutions for the church in managing plans and the realization of work programs that have been decided previously. This system designed by CodeIgniter Framework and MySQL as a database server. The system design using CodeIgniter Framework and MySQL as a database server. The results showed that system can accommodate the management of church work programs with the PDCA approach. From the user test results found that the system helps in controlling the work program of the church.